Diet,lifestyle pattern and health profile of professionals in software industry - Renjini R (Department of Home Science, College of Agriculture, 2009)
The present study on the ‘Diet, lifestyle pattern and health profile of professionals in software industry‘ was conducted to assess the socio–economic characteristics, dietary pattern, lifestyle and health profile of professionals. Hundred software professionals were selected from Technopark, Thiruvananthapuram, towards the study. A group of 50 professionals were taken as control group, with similar age, educational qualification and 5 years of experience status. The family back ground of the respondents revealed that, in both groups most of them belonged to nuclear families. Marital status of the respondents also showed that majority of them in both groups were unmarried. Educational status of the respondents indicated that in both groups majority of the respondents had completed their degree level of education and majority had an experience of 5 – 10 years in their occupation. The personal income of the IT respondents showed that majority had a monthly income between Rs. 50000 – 100000 and their monthly family income fell in the income group of Rs. 100001 – 200000. The assessment of social participation showed that majority of the respondents in both groups were not members in any organizations. Food consumption pattern of the respondents indicated that most of them were non-vegetarians in both groups and in IT group majority of the respondents were ‘night time nibblers’, some of them were ‘meal skippers’. Assessment of mean nutrient intake showed that among both groups energy, protein and fat intake was found to be well above the RDA. Morbidity pattern of the respondents portrayed that among IT group, majority had back pains, vision problems, shoulder pain and hyperlipidemia. But among the Non IT group, none of them were reported to have such complaints. Body Mass Index of the respondents revealed that majority of both groups were normal. Assessment of TST and WHR also revealed that majority among both groups had high TST and WHR. Assessment of stress level revealed that 2 percent of the IT respondents were found to have very high stress, and 4 percent had high stress. None of the Non IT respondents belonged this category. Nutritional status index of the respondents revealed that, among the IT group 44 percent of the IT male respondents had low NSI, while among IT female respondents 46 percent had low NSI.